Polystyrene biodegradation and functional biodiversity of gut microbial consortia in Tenebrio molitor with metagenomic and metabolomic insights - AFANDI AFANDI; SONY SUHANDONO; POPI SEPTIANI; AZZANIA FIBRIANI (Society for Indonesian Biodiversity, 2025)
Abstract. Afandi, Suhandono S, Septiani P, Fibriani A. 2025. Polystyrene biodegradation and functional biodiversity of gut microbial consortia in Tenebrio molitor with metagenomic and metabolomic insights. Biodiversitas 26: 3994-4016. Polystyrene (PS), a persistent plastic pollutant, can be biodegraded by Tenebrio molitor larvae through gut microbiome-mediated processes. This study employed integrated shotgun metagenomics and metabolomics to elucidate the microbial taxa, enzymes, and metabolic pathways involved in PS degradation. In vivo trials demonstrated a PS mass reduction of 6.38%, while in vitro experiments using gut microbial consortia resulted in a 3.49% mass loss. Surface erosion of the PS film was confirmed via scanning electron microscopy. Taxonomic profiling identified 334 bacterial genera under the PS diet and 329 under rice bran, with 93 genera unique to PS treatment. Dominant phyla included Proteobacteria (53.87%), Actinobacteria (6.44%), and Aquificae (6.42%). Hydrocarbon-degrading genera enriched under the PS diet included Burkholderia (3.94%), Nocardioides (2.67%), and Oceanobacter, the latter being exclusive to PS-fed larvae. Biodiversity metrics revealed high genus-level diversity (Shannon Index H? = 3.79-3.81), moderate Evenness (E = 0.65-0.66), and low Dominance (D = 0.06), indicating a complex yet balanced microbial ecosystem under xenobiotic stress. Functional annotations identified xenobiotic degradation pathways, including styrene metabolism (0.56%) and toluene metabolism (1.40%), driven by key enzymes such as monooxygenases and phenylacetaldehyde dehydrogenase. Metabolomic profiling identified 39 metabolites in larval frass and 20 degradation intermediates in the liquid medium, with lactic acid and benzyl alcohol being the primary products associated with the breakdown of aromatic compounds. These findings underscore the functional biodiversity and ecological adaptability of the gut microbiome in plastic detoxification, highlighting insect-microbe symbioses as promising agents for sustainable bioremediation strategies.